Analisis Pencapaian PPID Provinsi DKI Jakarta Dalam Meraih Penghargaan Keterbukaan Informasi Publik Tahun 2019 - Khansa Henovanto; Muhammad Mansur; Siti Ghina; Zahra Karyna Putri (Universitas Muhammadiyah Sorong, 2019)
A good government is one who applied transparency and accountability in their administration. This is similar to Indonesian law no. 14 of 2008 about Public Information Openness. This law has become an obligation for every government organization, including provincial government of DKI Jakarta. In 2019, DKI Jakarta has received an award from Information Commission by being one of the most government organizations that applied Public Information Openness. Moreover, DKI Jakarta has experienced being the most requested of any public informations. This research intends to find out what has provincial government of DKI Jakarta done until they reach the award. The result of this analysis is even though DKI Jakarta has reach its succeed, there is few things that needs to be considered, so that it can be evaluated by DKI Jakarta itself or any other provincial government, along with the goals that all of the governments will always apply and support Public Information Openness.